UTILIZATION OF TELEMETRY SYSTEMS IN QUAIL FARMING USING THE IOT CONCEPT - Mohammad Daffa Ananda; Yuliarman Saragih; Ridwan Satrio Hadikusuma (Jurnal Teknologi, 2023)
Poultry is one of the sectors that has grown significantly, especially in Indonesia, because poultry farms, especially quail, can provide crops in the form of nutritious meat and eggs. In the information obtained, quail meat production increased by 26.86%, and eggs decreased by 4.69%. In the literature study obtained, when raising poultry, sometimes they experience a condition called heat stress caused by the room's air temperature and humidity or cage exceeding the comfort zone limits on the quail's body. To overcome this, this research product was made by utilizing IoT technology. There needs to be more there. In this study, a telemetry system was also implemented to determine set point values to deal with extreme temperatures and humidity and provide set point values at mealtimes so that they were on time. The results of the discussion data when the research product was implemented obtained an average temperature and humidity of 29Â°C and 72.1%, then for the results of the value data without implementing the research product it was obtained with a temperature and humidity value of 32.5Â°C and 57.2%. The difference in temperature and humidity is 3.5 and 14.9, which is quite significant. It can be said that the implementation of research products into quail cages can minimize extreme temperatures in them. Apart from that, in this study, it was also advised to provide vitamins mixed into the quail drink at the appropriate dose so that the quails stay healthy during the specified period.